(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The aim of this paper is to increase the understanding of the opportunities and obstacles for developing entrepreneurial activities in agro-tourism sector in northern Montenegro. Therefore, this paper, thus, aims to set a framework for studying the role of innovations and entrepreneurship in the development of sustainable agro-tourism through identifying and providing suggestions for overcoming main entrepreneurial obstacles. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.